An underused opportunity to introduce ACE inhibitors and influence prognosis: observational study of patients undergoing aortic surgery. Issue 6 (7th May 2013) - Muttardi, Kayria; Haydar, Ali; Phua, Chee Kiang; Chapman, Neil; Jenkins, Michael; Cheshire, Nicholas JW; Bicknell, Colin D
Objective: To asses whether Angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) are underused in patients with aortic disease due to concerns regarding flow limiting (>70%) renal artery stenosis (RAS). Design: A prospective analysis of patients admitted for aortic surgery was performed (January–July 2009). Co-morbidity, ACEI/ARB use and renal function were recorded. Computerised tomography (CT) angiograms were reviewed by a single blinded radiologist for the presence and severity of RAS. Setting: St Mary's Hospital, Vascular Unit, Imperial College Healthcare NHS Trust, London, UK. Participants: 75 randomly selected patients admitted to our vascular unit including elective and emergency admissions. Main outcome measures: Indications for ACEI therapy were identified as determined by the National Institute of Health and Clinical Excellence (NICE) guidance. The ratio of the measurement distal to the stenosis and at the area of maximal stenosis on CT angiography were used to calculate the percentage RAS. Results: 60 patients were identified (15 patients excluded due to previously modified renal vessels). The median age was 73 [interquartile range 68, 77]. Their underlying aortic disease included 52 (87%) aortic aneurysm, 6 (10%) with aortic dissection, 1 (1.7%) patient with occlusive disease and 1 (1.7%) patient with mycotic disease. Overall, 56/60 (93%) patients had at least one indication for ACEI therapy. 33/60 (55%) of patients were already receiving ACEI. CT angiogram examination demonstrated 17/60 (28%) patients have RAS of some degree, of which only 9/60 (15%) have flow limiting RAS. Conclusion: A large proportion of aortic patients do not receive ACEI/ARB therapy despite definite indications and a low prevalence of flow-limiting RAS is low. After the exclusion of RAS at angiography, careful introduction of ACEI therapy with appropriate monitoring could be considered for many more patients.